2011
DOI: 10.1212/wnl.0b013e318221acee
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of pure subcortical vascular dementia using 11 C-Pittsburgh compound B

Abstract: SVaD without abnormal amyloid imaging was more common than expected. Patients with SVaD with and without abnormal amyloid imaging differed in clinical and MRI features, although there was considerable overlap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 25 publications
8
180
1
Order By: Relevance
“…As well as being a risk factor for spontaneous intracerebral haemorrhage (Samarasekera et al, 2012), CAA can result in cognitive deficits independently of AD (Arvanitakis et al, 2011;Boyle et al, 2015;Reijmer et al, 2015), although the exact interaction between these two processes remains unclear. Traditionally AD and SVCI have been described as having distinct neuroimaging profiles (Wardlaw et al, 2013b;Greenberg et al, 2014), but clinically differentiating between the two remains difficult, as both the cognitive symptoms and the imaging findings frequently overlap (Lee et al, 2011;Wardlaw et al, 2013a;Wardlaw et al, 2013b;Greenberg et al, 2014;Lee et al, 2014). Given this, identifying new markers that further improve our ability to discriminate between AD and SVCI remains both relevant and important, in particular with regard to recruitment for clinical trials investigating pharmacological interventions (Ahmed et al, 2014;Andrieu et al, 2015).…”
Section: Svci Subcortical Vascular Cognitive Impairment (Svmci and Svad)mentioning
confidence: 99%
See 1 more Smart Citation
“…As well as being a risk factor for spontaneous intracerebral haemorrhage (Samarasekera et al, 2012), CAA can result in cognitive deficits independently of AD (Arvanitakis et al, 2011;Boyle et al, 2015;Reijmer et al, 2015), although the exact interaction between these two processes remains unclear. Traditionally AD and SVCI have been described as having distinct neuroimaging profiles (Wardlaw et al, 2013b;Greenberg et al, 2014), but clinically differentiating between the two remains difficult, as both the cognitive symptoms and the imaging findings frequently overlap (Lee et al, 2011;Wardlaw et al, 2013a;Wardlaw et al, 2013b;Greenberg et al, 2014;Lee et al, 2014). Given this, identifying new markers that further improve our ability to discriminate between AD and SVCI remains both relevant and important, in particular with regard to recruitment for clinical trials investigating pharmacological interventions (Ahmed et al, 2014;Andrieu et al, 2015).…”
Section: Svci Subcortical Vascular Cognitive Impairment (Svmci and Svad)mentioning
confidence: 99%
“…Patients were considered PiB-positive if their global PiB retention ratio was over 1.5 from the mean of the normal control (Lee et al, 2011).…”
Section: Participantsmentioning
confidence: 99%
“…99m Tc-HMPAO SPECT is useful to differentiate CBD from other alternative diseases, because in CBD significant reduction of radiopharmaceutical uptake is in frontal, parietal, temporal cortices of the more affected side, in the thalamus and in pontocerebellar regions [30][31][32]34]. In vascular dementias, hypoperfusion is confirmed in bilateral thalami, the anterior cingulate gyrus, the temporal gyri, the caudate heads and the left parahippocampal gyrus, suggesting functional disconnection between frontal lobes and subcortical structures [31].…”
Section: Discussionmentioning
confidence: 99%
“…They found that ≈70% had no evidence of degenerative change in their brain and that these patients performed better on memory tasks than the Pittsburgh Compound B-positive patients. 10 …”
Section: Coexistence Of Degenerative and Vascular Changes In Vcimentioning
confidence: 99%